2022
DOI: 10.1002/btm2.10407
|View full text |Cite
|
Sign up to set email alerts
|

Fluid mechanical performance of ureteral stents: The role of side hole and lumen size

Abstract: Ureteral stents are indispensable devices in urological practice to maintain and reinstate the drainage of urine in the upper urinary tract. Most ureteral stents feature openings in the stent wall, referred to as side holes (SHs), which are designed to facilitate urine flux in and out of the stent lumen. However, systematic discussions on the role of SH and stent lumen size in regulating flux and shear stress levels are still lacking. In this study, we leveraged both experimental and numerical methods, using m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…By summarizing all the studies that reported WSS values at different locations of the ureteral stent in Table 2, our intention is to provide valuable insights into the fluid dynamics of the stent. The findings reveal that the proximal side holes exhibit WSS values below 0.001 Pa (2,33), indicating relatively low to moderate fluid shear forces in this region. The WSS increases toward the middle side holes, with values ranging from the order of 0.0001 Pa up to 0.1 Pa (2, 33), suggesting a notable enhancement in fluid shear stress.…”
Section: Values Of Wall Shear Stress Within the Stented Uretermentioning
confidence: 94%
See 3 more Smart Citations
“…By summarizing all the studies that reported WSS values at different locations of the ureteral stent in Table 2, our intention is to provide valuable insights into the fluid dynamics of the stent. The findings reveal that the proximal side holes exhibit WSS values below 0.001 Pa (2,33), indicating relatively low to moderate fluid shear forces in this region. The WSS increases toward the middle side holes, with values ranging from the order of 0.0001 Pa up to 0.1 Pa (2, 33), suggesting a notable enhancement in fluid shear stress.…”
Section: Values Of Wall Shear Stress Within the Stented Uretermentioning
confidence: 94%
“…Ureteral stents are indwelling medical devices commonly used to maintain the patency of the obstructed ureter to preserve/restore urine flow from the kidney to the bladder (1). A typical ureteral stent is a thin-walled polymeric tube with a length of 20-30 cm and an outer diameter ranging from 1.60 mm to 2.67 mm (2). A stent is equipped with small circular openings, known as side holes, that are often positioned throughout its length, allowing exchange of flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro model consisted of three components, the ureter model ( Zheng et al, 2022a ), the bladder model, and the urethra model. The ureter model was made by silicone molding, and was 270.6 mm long with a 4 mm inner diameter, including two conical ends to simulate the ureteropelvic junction (UPJ) and UVJ ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%